Penegakan Hukum Pelanggaran Administrasi Pemilihan Umum Dewan Perwakilan Rakyat Daerah Kota Tarakan Tahun 2024 (Pusat Riset dan Inovasi Nasional, 2026)
General elections constitute a fundamental pillar of Indonesia’s democratic system, functioning as a mechanism for the exercise of popular sovereignty and the protection of citizens’ voting rights. During the 2024 Regional People’s Representative Council (DPRD) election in Tarakan City, the Badan Pengawas Pemilu Kota Tarakan recorded twelve reports of alleged administrative violations throughout the electoral stages, including during the national vote recapitulation process. Of these reports, three allegations were proven, involving violations related to the Additional Voter List, the Special Voter List, and the eligibility requirements of candidates running for the Tarakan City DPRD in 2024. Essentially, election law enforcement serves as a safeguard to ensure fairness, legal certainty, and the protection of citizens’ constitutional right to vote. This study aims to examine the implementation of legal enforcement mechanisms against administrative violations in the 2024 Tarakan City DPRD election. A socio-legal research approach was employed to analyze both normative regulations and their practical application. Referring to Peraturan Bawaslu Nomor 8 Tahun 2022 concerning the Settlement of Administrative Violations of General Elections, the findings indicate that the Tarakan City Bawaslu holds authority in adjudicating and imposing sanctions on proven violations. As a result, one candidate, Erick Hendrawan Septian Putra, was disqualified from Electoral District 1. Furthermore, sanctions were imposed on the chairpersons and members of Polling Station 88 in Karang Anyar and Polling Station 2 in Pamusian for failing to carry out their duties as voting organizing groups in the election and subsequent processes.